It's time to sleep, it's time to dream - Adler, David A.; Chorao, Kay (New York : Holiday House, 2009)
A parent lulls a child to sleep with visions of soft spring breezes, lazy summer days, cool autumn winds, and moon-lit winter nights.
Kirkus Review.
1.5
K-3
Keywords: Bedtime -- Juvenile fiction; Parent and child -- Juvenile fiction; Seasons -- Juvenile fiction; Bedtime -- Fiction; Parent and child -- Fiction; Seasons -- Fiction; Bedtime -- Fiction; Parent-child relationship -- Fiction; Seasons -- Fiction